Epidemiology of Mycobacterium avium subsp. paratuberculosis (MAP) in the Northern dairy region of Antioquia, Colombia (2019)
ABSTRACT: Introduction: Paratuberculosis is an economically important, chronic, and incurable disease in ruminants, caused by Mycobacterium avium subsp. paratuberculosis (MAP). Since the effects of the disease represent a major source of losses for the milk-producing sector worldwide, it is important to define its impact and epidemiological dynamics both at regional and country-level. Objective: This cross-sectional study aimed to determine MAP herd-level prevalence, the herd level risk factors associated, the circulating genotypes, and to describe the spatial distribution and the environmental variables related to MAP in dairy herds of the Northern region of Antioquia, Colombia. Methods: Study herds (n = 386) located in 62 different districts from six municipalities were randomly selected amongst 7,794 dairies registered in the foot-and-mouth disease vaccination records from 2015. The sampling strategy considered proportional allocation, both at municipality and district-level. Participant herds were visited once between June and October 2016 to collect composite environmental samples and to complete a risk assessment questionnaire. The study herds were clasified in two groups, according to their productive system, those with under mechanical milking parlor and pasture grazing-based systems, and those under with in-paddock milking facilities. Each composite environmental sample contained material from six different sites of concentration of adult cattle and/or high traffic areas (e.g. areas surrounding waterers and feeders, areas surrounding the current mobile milking-unit places) and, depending on the production system, a second composite was collected from the perimeter of the manure storage lagoon (containing manure from the milking parlor). Identification of MAP was achieved using a duplex IS900-qPCR (Bactotype MAP PCR Kit®, Qiagen). A herd was considered as MAP infected if the environmental sample was positive in the qPCR. Information about the general characteristics of the herd, management practices, and knowledge about the disease was collected using the risk-assessment questionnaire. The information on risk factors was analyzed using a multivariable logistic regression model. Environmental samples from the 25 MAP-qPCR positive dairy herds were cultured by duplicate in Herrold´s egg yolk medium with mycobactin J to obtain isolates. Suspicious colonies were confirmed by MAP-qPCR. Positive DNA was sub-typed using mycobacterial interspersed repetitive units-variable number of tandem repeat (MIRU-VNTR) and multilocus short sequence repeats (MLSSR) techniques to analyze the genetic difference(s) between the isolates. To describe the spatial distribution and the environmental variables related to MAP, rainfall trends, day and nighttime surface temperature, and vegetation cover index were taken as environmental references of the physical background of the study area. Results: We found a herd-level prevalence of 4.1% (12/292; 95% CI: 1.8-6.4) and “having a history of mixed farming of cattle with other ruminants (i.e. sheep, goats) in the last 2 years” as a risk factor for MAP infection (OR = 3.9; 95% CI: 1.2-13.2) in 292 dairies under mechanical milking parlor and pasture grazing-based systems. On the other hand, we found a prevalence of 14.9% (14/94; 95% CI: 7.7-22.1) and “having other than Holstein breeds were predominant” (namely, Jersey, Jersey×Holstein crossbreeds, and Jersey×Swedish red crossbreeds) as a risk factor in 94 dairies with in-paddock milking facilities (OR = 3.7; 95% CI: 1.1-15.2). Sub-typing revealed two different genotypes by MIRU-VNTR (INMV 2 and INMV 36). MLSSR was carried out to increase the discriminatory power from what was obtained by MIRU-VNTR, but no differences were observed among the isolates recovered. According to the spatial distribution and the environmental analysis, an overall high rainfall regime was found in the study area. The daytime and nighttime surface temperature showed important variations during sampling months. No evidence of management of the vegetation cover was found. Conclusions: Our study reported the MAP prevalence in dairy herds from a representative dairy region in the Province of Antioquia (Colombia) and the possible relationship between MAP environmental positivity with the history of mixed farming of cattle with other susceptible ruminants and with the predominant breed of cattle in the herd. MAP genotypes INMV 2 and INMV 36 circulate in the study region. According to the spatial distribution and the environmental analysis, our study referred to an exploratory, non-experimental observational study carried out on an uncontrolled tropical and a real dynamic environment. Our purpose was to describe the general conditions of the environmental context where the detection of positive herds is most likely to happen, considering the same (or a very approximate) sample collection and handling, and molecular detection method. In general, our study represents an important approach to the knowledge on MAP epidemiological status in the Colombian dairy population of study.